Understanding spatially complex cryptic coloration in the green lynx spider Peucetia viridans. (9th February 2022) - Rodríguez, Zulay C.; Miller, Thomas E.; Holdridge, Erica M.
Abstract: Many species are thought to use cryptic coloration to evade predators or catch prey. However, colour patterns are historically difficult to document and compare when coloration is continuous and spatially complex. The authors studied colour variation in the green lynx spider, Peucetia viridans, a sit‐and‐wait predator often found in the tops of inflorescences feeding on pollinators. Spiders were collected from three distinct plant species that provided different original colour backgrounds and photographed under standard lighting and background. A novel colour analysis method (Colormesh) was used to quantify spatially explicit contributions of red, green, and blue along the spider abdomen from digital photographs. Spiders collected from green backgrounds were found to have significantly greater contributions of green abdomen colours; red and blue body colours showed no significant correlation with spider background. This is the first study of colour‐matching in a natural population of this wide‐spread generalist predator and also demonstrates a novel method for quantifying complex, continuous colour patterns. Abstract : 1. A new method is used to quantify colour patterns on organisms in a spatially explicit form. This method is used to investigate colour variation in a spider. 2. The authors asked if spiders that occurred on flowers and leaves of very different colours demonstrated significantly different colour patterns. 3. The spiders were found to have more green coloration in particular locations when found on green leaves, while less green when found on purple or white flowers.